2019
DOI: 10.1021/acsami.9b02115
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and High-Throughput Polyelectrolyte Complex Membranes via Phase Inversion

Abstract: High-flux filtration membranes constructed through scalable and sustainable methods are desirable for energy-efficient separations. Often, these criteria are difficult to be reconciled with one another. Polymeric membranes can provide high flux but frequently involve organic solvents in processing steps. Solubility of many polymeric membranes in organic media also restricts their implementation in solvent filtration. In the present work, we report a simple and high-throughput aqueous processing approach for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 49 publications
(110 reference statements)
1
73
0
Order By: Relevance
“…In addition to saloplastics mentioned above, PE complexation has been used by Sadman et al to prepare porous membranes. 46 In their work, PECs were obtained by mixing two strong PE solutions. After PECs were extruded and treated with salt water annealing, they were partially dissolved at varying salt solutions to obtain coacervates and then cast into thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to saloplastics mentioned above, PE complexation has been used by Sadman et al to prepare porous membranes. 46 In their work, PECs were obtained by mixing two strong PE solutions. After PECs were extruded and treated with salt water annealing, they were partially dissolved at varying salt solutions to obtain coacervates and then cast into thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, known as salt switch, is potentially useful for a variety of purposes, such as controlling the porosity of polyelectrolyte complex-based hydrogels, membrane fabrication via phase inversion, and hardening an injectable coacervate-based underwater adhesive. [38][39][40][41] The latter strategy is partly inspired by sandcastle worms which inject their glue components in a liquid state followed by insitu coacervation leading to a highly-wetting, low interfacial tension coacervate immiscible with seawater (note that, given the high ionic strength of seawater, the worm mainly takes advantage of an abrupt change in pH and ionic composition as well as oxidative post-curing of catechol moieties to set the glue). 4,42 Given the relatively low ionic strength of the human body (with 0.137 M NaCl and traces of other salts), a salt switch into physiological conditions is potentially useful for biomedical applications such as embolization, sealing leaks, and tissue adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…De Vos also demonstrated a first example, where polyelectrolyte complexation leads to phase separation to produce freestanding membranes. Sadman et al recently reported a similar approach based on polyelectrolyte complexation achieved by using salt concentration as a trigger . Membranes with pore sizes ranging from microns to several hundred nanometers were prepared by dissolving a PEC in KBr salt solution to form a complex coacervate.…”
Section: Introductionmentioning
confidence: 99%
“…Although the process eliminates the use of organic solvents, the downsides were that it is time‐consuming because it requires extensive solution preparation and includes a two‐step coagulation process. Moreover, the complex coacervates require an equilibration time ranging from 1 day to 1 month . But most importantly, limited control over pore size and geometry was reported.…”
Section: Introductionmentioning
confidence: 99%